2020
DOI: 10.3390/ijms21207572
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the Transcriptome and Metabolome of Cecropia obtusifolia: A Plant with High Chlorogenic Acid Content Traditionally Used to Treat Diabetes Mellitus

Abstract: This investigation cultured Cecropia obtusifolia cells in suspension to evaluate the effect of nitrate deficiency on the growth and production of chlorogenic acid (CGA), a secondary metabolite with hypoglycemic and hypolipidemic activity that acts directly on type 2 diabetes mellitus. Using cell cultures in suspension, a kinetics time course was established with six time points and four total nitrate concentrations. The metabolites of interest were quantified by high-performance liquid chromatography (HPLC), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 89 publications
0
21
0
1
Order By: Relevance
“…We investigated two well-characterized genotypes at two stages for their different CGA accumulation ( Fig 2A–2C ). Although a few genes involved in CGA biosynthesis had been reported in other plant species, such as tomato [ 21 , 22 ], Arabidopsis [ 23 , 24 ], Nicotiana tabacum [ 27 ], Lonicera japonica [ 50 , 51 ], Sunflower [ 52 ], Dandelions [ 53 , 54 ], Cecropia obtusifolia [ 55 ], the molecular mechanisms underlying in leafy sweet potato remains largely unknown. In the present study, a total of 29834 genes were identified based on the reference guided transcriptome analysis of two genotypes at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated two well-characterized genotypes at two stages for their different CGA accumulation ( Fig 2A–2C ). Although a few genes involved in CGA biosynthesis had been reported in other plant species, such as tomato [ 21 , 22 ], Arabidopsis [ 23 , 24 ], Nicotiana tabacum [ 27 ], Lonicera japonica [ 50 , 51 ], Sunflower [ 52 ], Dandelions [ 53 , 54 ], Cecropia obtusifolia [ 55 ], the molecular mechanisms underlying in leafy sweet potato remains largely unknown. In the present study, a total of 29834 genes were identified based on the reference guided transcriptome analysis of two genotypes at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, HCT2 has also been associated with CGA biosynthesis in Cecropia obtusifolia and Populus . In the latter, HCT2 is involved in the defense response via the WRKY transcriptional regulatory pathway (Cadena‐Zamudio et al, 2020; Zhang et al, 2018). Based on these observations, we suggest that HQT or HCT is a key enzyme that may recognize an acyl acceptor, quinic acid or shikimic acid to determine CGA biosynthesis in salt‐treated K. caspia (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, integrated transcriptome and metabolome analysis are effective ways to explore the relationship between genes and metabolites (Cadena‐Zamudio et al., 2020; Peng et al., 2020). For example, transcriptome and metabolome assayed from 580 tomato ( Solanum lycopersicum L.) lines revealed genomic loci associated with hundreds of transcripts and metabolites, thus establishing a framework for metabolism and pathogen resistance during tomato fruit ripening and providing insights into essential fruit quality traits (Szymanski et al., 2020).…”
Section: Introductionmentioning
confidence: 99%